2014
DOI: 10.1016/s0140-6736(13)62159-5
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemotherapy for non-small-cell lung cancer: a systematic review and meta-analysis of individual participant data

Abstract: SummaryBackgroundIndividual participant data meta-analyses of postoperative chemotherapy have shown improved survival for patients with non-small-cell lung cancer (NSCLC). We aimed to do a systematic review and individual participant data meta-analysis to establish the effect of preoperative chemotherapy for patients with resectable NSCLC.MethodsWe systematically searched for trials that started after January, 1965. Updated individual participant data were centrally collected, checked, and analysed. Results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
282
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(291 citation statements)
references
References 40 publications
(69 reference statements)
1
282
2
6
Order By: Relevance
“…This accounts for a 5% absolute increase in survival over surgery alone. 3 Second, a neoadjuvant approach provides a discovery platform for in vivo assessment of tumor response. Third, tissue available pre- and post treatment allows for translational studies and the utilization of surrogate endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…This accounts for a 5% absolute increase in survival over surgery alone. 3 Second, a neoadjuvant approach provides a discovery platform for in vivo assessment of tumor response. Third, tissue available pre- and post treatment allows for translational studies and the utilization of surrogate endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…This result seems to be in concert with meta-analyses indicating an absolute 5-year survival benefit of about 5% for neoadjuvant chemotherapy [24, 25]. Despite limitations in comparing the data of meta-analyses on pre- and postoperative chemotherapy, the benefit of preoperative chemotherapy seems to be similar to the benefit of adjuvant approaches, allowing the suggestion that the relative effects of neoadjuvant and adjuvant systemic therapy are comparable.…”
Section: Discussionmentioning
confidence: 71%
“…A meta-analysis of 15 trials (2385 patients) demonstrated significant but modest improvements in overall survival at 5 years from 40 to 45% (HR 0.87, 95% CI 0.78–0.96, P=0.007), time to distant recurrence at 5 years improved from 60% to 70% (HR 0.69, 95% CI 0.58–0.82; p<0.001) and a recurrence free survival improvement from 30% to 36% at 5 years across all stages (HR 0.85, 95% CI 0.76–0.94, P=0.002). 7 In addition to providing benefit to patients by potentially improving overall survival and reducing the risk of disease recurrence, evaluation of the tumor response to targeted therapy in the neoadjuvant setting provides an excellent opportunity to study residual disease, given that patients undergo definitive surgical resection as a predetermined part of their treatment plan. Tissue-based molecular evaluations of targeted therapy response in neoadjuvant treatment of early stage NSCLC have not been performed.…”
Section: Discussionmentioning
confidence: 99%